(untitled) (Heritage, 2024)
The paper examines the influence of (neo)liberal elites on the etatization, i.e. deetatization of cultural policy in Serbia, starting from the definition of public policies as a relatively stable, purposeful course of action of state bodies, public officials, governmental and legislative bodies in dealing with certain problems or issues that affect a significant number of people. The aim of the paper is to analyze the interrelationship between the ideas of (neo)liberal elites about the role of the state in conducting cultural policy, the practical activities of the legislative and executive authorities and the achieved results. The focus is on the achieved results of transitional cultural policies in Serbia after the 2000 elections, but also on the comparison with previous transitional milestones that were influenced by (neo)liberal elites, such as liberal patriots to the St. Andrew’s National Assembly (19th century) and Yugoslav liberal dissidents to self-management in culture (20th century). Observed from the point of view of the role of the state in conducting cultural policy in Serbia, from the 19th century until today, we see that the phases of etatization and deetatization alternated depending on the geopolitical attitudes of those actors who had the most influence on decision-making in the field of culture. In this sense, the role of liberal elites in the cultural and political history of Serbia is significantly different, since one group advocates for the restoration of statehood and the strengthening of the role of the political, scientific and cultural institution of the state, while the other group contributes to the corruption of the state and the collapse of state power by building the double state model of public policies. Thus, "liberal patriots" strengthen the role of a free and sovereign state based on right of the people, while the post-Yugoslav political, intellectual, cultural and artistic left-liberal Eurocentric civic elite bases its policy on deetatization which means the reduction of the role of the state and increasing the role of the cosmopolitan highly educated intellectual elite. The key difference is that the liberal patriots laid permanent foundations of democratic political, scientific, cultural and educational institutions, the post-Yugoslav neoliberal elite dismantles those foundations and weakens cultural institutions.